Mengintegrasikan Permainan Ular Tangga Baduy Menggunakan Model ADDIE Sebagai Alternatif Media Pembelajaran Bangun Datar Berbasis Nilai-Nilai Kearifan Lokal Baduy - Burhanudin, Burhanudin; Arisetyawan, Andika (Universitas Pendidikan Indonesia Kampus Serang, 2021)
In practice, learning media use is still rarely used, and the integration of culture in the mathematics teaching media for two-dimensional figure materials is still minimal. It is the basis for researchers to develop learning media for snakes and ladders based on Baduy culture, integrated with two-dimensional figure materials. This study aims to create learning media based on the local wisdom of Baduy that can attract students' motivation in learning mathematics with the two-dimensional figure. The research subjects are grade IV students. The method used is ethnography. Ethnographic methods are used to collect information related to Baduy culture. Data collection techniques used interviews, observations, and documentation studies. Then, after all the data were collected, the researcher used the ADDIE model to develop learning media. The steps taken are. In the analysis stage, the researcher performs task analysis, identifies problems, and analyses needs. The researcher designed the learning media framework and materials based on research and data on local wisdom of Baduy culture in the design phase. In the development phase, researchers developed a media framework and teaching materials and then validated them. The implementation stage conducted a trial of media and teaching materials with 13 students as the subject at SDN Gelam 2. The evaluation stage made product improvements based on the results of the trial of teaching materials. From this stage of development, the researcher concluded that the media and teaching materials that were made could attract students' learning motivation and could be used in learning two-dimensional figure materials for grade IV elementary school. The results of this study are the Learning Implementation Plan (RPP), Student Worksheets, Baduy Snakes and Ladders Learning Media, and learning evaluation questions